2017
DOI: 10.1111/1751-2980.12453
|View full text |Cite
|
Sign up to set email alerts
|

Echoendoscopic ablative therapy for solid pancreatic tumors

Abstract: Initially, endoscopic ultrasound (EUS) was developed to inspect the pancreas and other organs adjacent to the gastrointestinal tract. After introduction of curvilinear-array echoendoscopes, EUS has been used for a variety of interventions in gastroenterology, including fine needle aspiration, pancreatobiliary drainage and tumor ablation. EUS-guided ablation of pancreatic cystic tumors with ethanol and with or without cytotoxic agents has been studied, showing its potential to become an alternative to surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…PC therapy is an arduous challenge for thermal ablation from anatomical consideration. Only limited studies have reported the application of ablation in experimental and clinical setting in the management of solid and cystic PC, including radiofrequency, microwave, ethanol ablation, high-intensity focused US, cryoablation and irreversible electroporation technique [5,6,9,[23][24][25][26]. Among them, radiofrequency, cryoablation and ethanol ablation were most commonly used methods for unresectable PC [27].…”
Section: Discussionmentioning
confidence: 99%
“…PC therapy is an arduous challenge for thermal ablation from anatomical consideration. Only limited studies have reported the application of ablation in experimental and clinical setting in the management of solid and cystic PC, including radiofrequency, microwave, ethanol ablation, high-intensity focused US, cryoablation and irreversible electroporation technique [5,6,9,[23][24][25][26]. Among them, radiofrequency, cryoablation and ethanol ablation were most commonly used methods for unresectable PC [27].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding pancreatic solid neoplasms, small functioning pancreatic neuroendocrine tumors (PNETs) of <2 cm are the most appropriate indication for EUS-guided ablation therapy. Functioning PNETs have hormone-related symptoms and malignant potential [ 19 ]. As functioning NETs are usually small and sometimes manifest as multiple lesions [ 27 ], EUS-guided ablation therapy can be considered as a complementary tool to surgical resection.…”
Section: Indication Of Eus-guided Ablation Therapymentioning
confidence: 99%
“…As functioning NETs are usually small and sometimes manifest as multiple lesions [ 27 ], EUS-guided ablation therapy can be considered as a complementary tool to surgical resection. Evaluation of treatment response after ablation therapy of functioning PNETs can be performed by assessing the improvement of hormone-related symptom and/or with serial hormonal assays [ 15 , 16 , 19 ]. EUS-guided ablation therapy for small nonfunctioning PNETs and solid pseudopapillary neoplasms is also under investigation.…”
Section: Indication Of Eus-guided Ablation Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Following different survival periods (0-4 days) in the interventional group (n=3), open pancreatectomy was carried out. The control group (n=4) included open pancreatectomies in two pigs with non-treated pancreases and in two with pancreatic RFA on the same day 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 .…”
mentioning
confidence: 99%